1994
DOI: 10.1002/pi.1994.210330208
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(methyl methacrylate) star polymers

Abstract: Star‐branched poly(methyl methacrylate)s (PMMA) were synthesized by linking ‘living’ arms (produced by anionic polymerzation) with ethylene glycol dimethacrylate. Stars having arm molecular weights of 10000 and 40000 and between 4.9 and 18.7 branches were produced. The polymers were characterized using light scattering, size exclusion chromatography, and viscometry. It was found that well‐defined PMMA stars were obtained only at the higher (40000) arm molecular weight. The stars prepared using the lower molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Star polymers can be obtained through the ''arms first'' approach, [4] in which the living linear arms of the star polymers were prepared first and then the arms were reacted with a multi-functional core to result in star polymers. On the other hand, a surfaceinitiated polymerization from a multi-functional initiator, which served as a core for star polymers, provided another approach called the ''core first'' method.…”
Section: Introductionmentioning
confidence: 99%
“…Star polymers can be obtained through the ''arms first'' approach, [4] in which the living linear arms of the star polymers were prepared first and then the arms were reacted with a multi-functional core to result in star polymers. On the other hand, a surfaceinitiated polymerization from a multi-functional initiator, which served as a core for star polymers, provided another approach called the ''core first'' method.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the RI and ing DVB linking of polystyrene arms, 20,21 and for UV traces of the residual arm fraction showed ethylene glycol dimethacrylate linking of polythat although the majority never crossed to DVB, (methyl methacrylate) arms by group transfer poa pronounced UV signal suggested that a signifilymerization. 22 cant fraction of residual arms did cross to DVB, Table II shows that except for the star polymer yet failed to become linked into a star. This suggested that the relatively poor linking efficiency in this case was an inherent consequence of the longer arm, but might have been exacerbated by the slightly premature addition of DVB at only 89% IB conversion.…”
Section: Resultsmentioning
confidence: 96%
“…Divinylbenzene was used by Rempp and collaborators 29 to prepare poly(tertbutyl acrylate) (PtBuA) stars by anionic polymerization. Efstratiadis et al 30 used EGDM to link anionically prepared living PMMA chains, thus forming star polymers. More recently, Ueda et al 31 synthesized bi-and trifunctional dichloroacetates via living radical polymerization techniques.…”
Section: Introductionmentioning
confidence: 99%